Novel Translation for Sustainable Vertical Housing in Urban Environment - Anastasia M. D. Setyo Murni; FX Teddy Badai Samodra (Institut Teknologi Sepuluh Nopember, 2018)
Urban housing has already led vertical development such as the improvement for slum settlement. In fact, this solution has not been considered optimal and even cause other problems. This study offers the concept of a vertical kampung by applying the translation of the identity of a traditional value. Sustainable design methods with field measurements, interviews and design simulations using Ecotect analysis-RADIANCE and ANSYS Fluent software as an integrated environmental consideration with the completion of social and economic sustainability were conducted. The results show that new methods using sustainable architectural principles should also be done. In addition, design of affordable dwelling from slums environment can also be transformed into new user empowerment and carrying capacity for the city.